Synthesis Characterization and Antimicrobial Activity of Metal Chelates of 1, 7-Di (2-hydroxyphenyl) 1, 7 di (N-methyl) aza-1, 3, 5 heptarine-3-ol hydrochloride - Nalin P. Patani; M. V. Hathi (E-Journal of Chemistry)
The Schiff base complexes derived from 2-furancarboxaldehyde and N-methyl-2-amino phenol have been prepared and characterized using several physical techniques, like elemental analysis, thermogravimetric analysis, magnetic moment measurements, infrared and resonance spectra. N-Methyl-2-amino phenol was condensed stoichiometrically with 2-furancarboxaldehyde in presence of methanol. The resulting 1,7-di(2-hydroxyphenyl) 1,7 di(N-methyl) aza-1,3,5 heptarine-3-ol hydrochloride was characterized by elemental analysis and spectral studies. The transition metal complexes of Cu2+, Zn2+, Ni2+, Co2+ and Mn2+ of the synthesized complexes were prepared. Metal ligand (M:L) ratio, IR, reflectance spectral studies, magnetic properties and antimicrobial activity of the synthesized complexes and its metal complexes were carried out.